«The Ball Lightning»: Physics Base & Conceptual Views Complex - A. V. Pinchuk; V. A. Pinchuk (Eurasian Chemico-Technological Journal, 2009)
The complex of conceptual views about ball lightning (BL) as containing surplus electrical charge quasi-stationary material foundation with distinctions between levels of translation temperature and exciting temperatures of chemical bonds and electron energy states has been offered and is substantiated in the paper. The being formed complex is grounded upon overstepping the limits of generally accepted physical base and is aimed at all-round substantiation of jointly observed in nature manifestations ob BL. Within the limits of the being formed complex the possibility of localization of ball lightning in airspace is confirmed. The nature of the one’s radiate capacity is substantiated. The role of environment as source that feeds BL with energy is established. Power supply mechanisms, conditions and peculiarities of BL’s characteristics reproduction through lifetime are specified. The formations channels of energy resources of BL are turned out. Levels of BL’s energy potentialities, both permissibility proper and wide diapason of variation of the ones (multi-faces of ball lightning) are substantiated. Adequacy of being formulated conceptual views as a whole is confirmed.